2012
DOI: 10.1096/fasebj.26.1_supplement.798.23
|View full text |Cite
|
Sign up to set email alerts
|

ATP release is altered in a mouse model for Duchenne muscular dystrophy and signals for proteins that promote cell death

Abstract: Several reports have described changes in ATP signaling in models for muscular dystrophy; nevertheless, none of them has been directly related with the dystrophy pathology. To study this pathway we used muscle fibers from flexor digitorum brevis isolated from normal and mdx mice. ATP was measured using luciferase, protein expression by Western blots and mRNA by qPCR. The basal ATP release occurs in bursts peaking every 5 minutes in fibers from both mice, being several fold more important in mdx fibers. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ATP sensitivity has been reported to be much higher in mdx mice [ 89 ]. It has been shown that the release of ATP is greater in mdx mice, while the expression of P2Y 2 receptors is increased, and the expression of P2Y 1 receptors is reduced [ 90 ]. It was also found that suramin, which leads to the normal expression of P2Y 2 receptors, improved the clinical picture of Duchenne dystrophy [ 91 ].…”
Section: Purinergic Signaling In Duchenne and Becker Dystrophiesmentioning
confidence: 99%
“…ATP sensitivity has been reported to be much higher in mdx mice [ 89 ]. It has been shown that the release of ATP is greater in mdx mice, while the expression of P2Y 2 receptors is increased, and the expression of P2Y 1 receptors is reduced [ 90 ]. It was also found that suramin, which leads to the normal expression of P2Y 2 receptors, improved the clinical picture of Duchenne dystrophy [ 91 ].…”
Section: Purinergic Signaling In Duchenne and Becker Dystrophiesmentioning
confidence: 99%